PENGARUH LINGKUNGAN SEKOLAH TERHADAP MINAT BELAJAR MATA PELAJARAN IPA PESERTA DIDIK KELAS V SD NEGERI 1 MARGA AGUNG - Pramesta, Sekar Ayu; Mashari, Ali; Soraya, Rahayu (AHSANTA JURNAL PENDIDIKAN, 2024)
The problem in this research is that students' interest in learning is still low. This is proven by many students who are not enthusiastic when studying at school or during the learning process. This research aims to determine whether or not there is an influence of the school environment on the interest in learning science subjects of class V students at SD Negeri 1 Marga Agung, South Lampung Regency. This research uses quantitative methods. The population in this study was 30 students and the samples taken from this research were all students in class V of SD Negeri 1 Marga Agung, South Lampung Regency, sampling used a saturated sample. The instrument used to collect data was a questionnaire in the form of a Likert scale with 20 statements. The results of the validity test of 20 school environment questionnaire statements were 2 statements declared invalid and 18 statements declared valid, of the 20 statements on the interest in learning questionnaire there was 1 statement declared invalid and 19 statements declared valid. The reliability test of the school environment questionnaire was 0.920 and the learning interest questionnaire was 0.925 (high). Data analysis techniques use linearity normality test, t-test, and simple linear regression test. From the results of the research carried out by the researcher, it can be seen that testing the hypothesis testing were 0,995 > 0,361 with a significance level (Sig.) 0.000 < 0.05. This means that is accepted and is rejected. Thus, there is an influence of the school environment on the interest in studying science subjects of class V students at SD Negeri 1 Marga Agung, South Lampung Regency.